Sexually transmitted diseases-related knowledge levels of midwifery students studying at two different universities: A comparative study - Yesiltepe, Akgun; Ulucan, Mihriban; Akan, Aysenur; Can, Hafize Ozturk (Womens Health & Action Research Centre, 2025)
This study aimed to compare the knowledge levels of midwifery students from two universities in eastern and western Turkey regarding sexually transmitted diseases (STDs). A descriptive, comparative study was conducted with midwifery students from both regions.The average score on the STD Knowledge Test was 14.49 +/- 3.83. Students from the western university scored 14.63 +/- 3.60, while those from the eastern university scored 13.98 +/- 4.58. Among western university students, knowledge scores were significantly associated with factors such as year of study, place of residence, and prior sexual health education. For eastern university students, significant factors included age, year of study, social security status, and university-based sexual health education (p<0.05). It is recommended that educational programs be strengthened to enhance students' knowledge and improve access to accurate, reliable information. (AfrJReprod Health 2025; 29 [7]: 48-58).
Keywords: Sexually transmitted diseases; Midwifery; Knowledge; Student